Diagnostic Methods on the Study of Children at the School Preparation Stage in Poland - Khrystyna Mykyteychuk; Valentyna Zvozdetska (Pedagogical Discourse, 2020)
The current focus of the European educational strategy on the obligation to involve children in pre-primary education actualizes the problem of preparing the child for school and the pre-school education functioning, modernizes and updates the content and technology of pedagogical activity at this stage. As a result of educational reforms in Poland, mandatory pre-school training for children has become compulsory. Pedagogical diagnostics is the essence of this stage where it is not a psychologist but a preschool institution teacher, in the context of daily pedagogical interaction with children, implements a systematic observation and interprets children's achievements in relation to the school maturity criteria. The studied materials show that special diagnostic techniques, tools and clear procedural instructions for teachers were created for this purpose. On the basis of a retrospective analysis, the evolutionary development in the field of Polish pedagogy the problem of diagnosing children's readiness for school education is highlighted. Diagnostic methods are systematized according to chronological principle, their content and procedural aspects are characterized. It is grounded that, as a result of diagnostic techniques mastering, tools knowledge and ability to perform diagnostic procedures, the teacher is able to determine the degree of mental and social development of the child, which contributes to the school tasks, as well as the factors that determine this development. The teacher creates a comprehensive profile of the child in terms of his/her knowledge and competences, and on that basis develops a strategy of pedagogical influence and interaction with the child at the beginning of school.